Perception of Water Quality in Rural/Agricultural Areas of Machakel District, North West Ethiopia - Mulugeta Temesgen Bayeh; Alemu Azmeraw Bekele (International Journal of Agriculture System, 2018)
Potable water with high quality is a basic requirement for human wellbeing. However, the perceptions on the quality of potable water sources and associated factors influencing the later have not been well studied. Hence, this study aims at examining the perception of water quality in rural/agricultural areas of Machakel district, North West Ethiopia. The study used cross sectional survey design. structured interviews with 293 sample respondents, who were selected using probability sampling technique, were conducted to capture their views on water quality at the source. Descriptive statistics and ordinal logistic regression were used to identify factors affecting the perception of households on water quality in rural/agricultural areas. Most of the household heads used protected hand-dug well, protected spring and protected shallow well. Variables such as education, income, past experiences of health risks, chemicals (chlorine) and poor trust in supplier have a significant effect on perception of rural agricultural communities on water quality at the source. The study suggests education and chlorination of water sources to be promoted among the rural/agricultural communities to enhance better quality perception on potable water sources. On the other hand water quality control systems should be created to avoid health jeopardy from water born sickness. For high income groups it may be better to provide access to pipe water. User participation should be considered in the process of water source construction.